From the Border to Education: Developing a Local Resource Potential Booklet as a Learning Media - Andrinata Andrinata; Arfita Rahmawati; Bella Theo Tomi Pamungkas; Agustinus Hale Manek; Martina Ayu Sejati; Popy Haryani (International Journal of Social Learning (IJSL), 2026)
Malaka Regency, which borders Timor-Leste, faces challenges in utilizing its natural resources, thus requiring learning media to explore local potential. This study aims to develop a learning booklet based on local renewable energy sources and test its effectiveness. This study employed a research and design model developed by Borg and Gall. For analysis, N-Gain was used to evaluate pre-test and post-test results, involving 98 eighth-grade students and 27 social studies teachers in the dissemination stage. The results showed a significant increase in student understanding with an N-Gain of 0.6647 (66.47%), which is considered effective. A paired t-test revealed a highly significant difference between pre-test and post-test scores (p < 0.001), with an effect size (Cohen's d = 2.568) indicating a substantial impact. 78.15% of teachers considered the booklet suitable for classroom use. These findings indicate that the developed booklet is effective and pedagogically appropriate.